Judicial Breakthrough in Investor Protection: Expanding the Legal Standing of Good-Faith Stock Buyers in Indonesia - Muhammad Syamil Fasya (Politeknik Siber Cerdika Internasional, 2026)
Background: Under Indonesian Company Law (UUPT), a good-faith investor who has fully paid for shares but whose name is not recorded in the Company’s Shareholders Register (Daftar Pemegang Saham/DPS) does not have legal standing to apply to the court to compel a General Meeting of Shareholders (GMS). Objective: This article analyzes how the North Jakarta District Court decision No. 530/Pdt.G/2024/PN Jkt. Utr addresses this legal gap by recognizing the standing of an unregistered foreign investor acting in good faith, thereby providing judicial clarification in shareholder protection. Methods: This study employs a normative legal research method using both case and conceptual approaches. It analyzes primary legal sources, including the court decision, UUPT, KUHPerdata (Indonesian Civil Code), and relevant legal doctrines. Results: The court applied rechtsvinding (legal discovery) and analogy-based reasoning to correlate the rights under Article 80 of the UUPT with those of a de facto shareholder based on substantive ownership, despite the failure to register in the DPS due to alleged bad faith by third parties. In this context, the voluntair petition mechanism proved more effective than a contentiosa lawsuit in addressing the dispute. Conclusion: The decision represents a progressive step in strengthening investor protection, yet it remains a stop-gap measure. Judicial activism should be approached cautiously, as legislative reform of the UUPT is still required to formally codify such protections.